Individual and relational risk factors for the development of eating disorders in adolescent aesthetic athletes and general adolescents - Francisco, Rita (2013)
This study compared potential risk and protective factors, levels of disordered eating (DE), and their relationship among young aesthetic athletes (elite and non-elite) and controls (N = 725; 62.5 % females; mean age = 15.3, SD = 2.1). The participants completed self-report measures (McKnight Risk Factor Survey-IV, Contour Drawing Rating Scale and Eating Disorder Examination-Questionnaire). Female elite athletes showed a greater risk of developing eating disorders than non-elite athletes and controls, with no difference between the three groups of males. Multiple group analyses revealed important differences in DE predictors. Although social pressure is the strongest DE predictor in non-elite athletes and controls, in elite athletes, the strongest DE predictor is body image dissatisfaction. Parental influences, rather than self-esteem, are predictors of DE in elite athletes, unlike the other two groups. These results show that the risk and protective factors involved in the development of DE are not universally valid. The results highlight the importance of studying specific characteristics associated with DE in aesthetic athletes. Some implications for ED risk assessment and prevention are discussed.